Mining the source of resistance for downy mildew and gummy stem blight in bottle gourd (Lagenaria siceraria) accessions - BHARDWAJ, D R; GAUTAM, K K; SAHA, S; NAGENDRAN, K; PANDEY, K K; SINGH, A K; SINGH, P M; SINGH, B (The Indian Journal of Agricultural Sciences, 2018)
Bottle gourd [Lagenaria siceraria (Mol.) Standl.] is an important vegetable crop widely cultivated during summer and kharif season throughout the country. Seventeen advance lines of bottle gourd were artificially screened for downy mildew. Among them, only VRBG-12 showed resistance with lowest PDI value of 6.5%. Three lines (VRBG-26, VRBG-47 and VRBG-17) were moderately resistant (15.7-21.7%), four (VRBG-11, VRBG-20, VRBG-49 and VRBG-56) moderately susceptible (30.4-40.2%), five (VRBG-52, VRBG-5, VRBG-10, VRBG-66 and VRBG-53) susceptible (59.3-69.2%) and the remaining four lines (VRBG-33, VRBG-48, DVBG-01 and VRBG-61) were highly susceptible (79.2-90.75%). Fifty one accessions were screened against gummy stem blight and none were found immune/resistant under field condition. Out of 51 lines, least severity (28.8%) was observed in VRBG-556, 13 were moderately susceptible with the PDI ranging between 28.80 to 49.44, 32 were found to be susceptible (50.4-74.4%) and 6 highly susceptible (75.2-87.2%). These potential genotypes can be used further in breeding programs of bottle gourd against downy mildew and gummy stem blight.